2015
DOI: 10.1136/bmjopen-2015-007626
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in out-of-hospital cardiac arrest survival outcomes between two metropolitan communities: Seoul-Osaka resuscitation study

Abstract: ObjectivesThe objective of this study was to compare the temporal trends in survival after out-of-hospital cardiac arrest (OHCA) between two large metropolitan communities in Asia and evaluate the factors affecting survival after OHCA.DesignA population-based prospective observational study.SettingThe Cardiovascular Disease Surveillance (CAVAS) project in Seoul and the Utstein Osaka Project in Osaka.ParticipantsA total of 36 292 resuscitation-attempted OHCAs with cardiac aetiology from 2006 to 2011 in Seoul an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
(24 reference statements)
1
13
1
1
Order By: Relevance
“…This change in performance rates is consistent with statistics on cardiac arrest patients of all ages in Seoul, including elderly patients 24,27) . The number of lay people educated about CPR for each 100,000 Seoul citizens rose each year, from 2,143 in 2010, while the number of people registered as citizens performing CPR on cardiac arrest patients with good faith (CPR supporters) reached 26,000 24) .…”
Section: Discussionsupporting
confidence: 74%
“…This change in performance rates is consistent with statistics on cardiac arrest patients of all ages in Seoul, including elderly patients 24,27) . The number of lay people educated about CPR for each 100,000 Seoul citizens rose each year, from 2,143 in 2010, while the number of people registered as citizens performing CPR on cardiac arrest patients with good faith (CPR supporters) reached 26,000 24) .…”
Section: Discussionsupporting
confidence: 74%
“…In recent years, the survival rate from out‐of‐hospital cardiac arrest (OHCA) in industrialized countries has increased because of major advances in cardiopulmonary resuscitation (CPR) . However, the mortality rate remains high, and the survival to hospital discharge rate among OHCA patients is between 7.2% and 11% . Studies have shown that the survival rate declines rapidly when the duration of CPR surpasses 10 minutes and even more rapidly if it exceeds 30 minutes .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] However, the mortality rate remains high, and the survival to hospital discharge rate among OHCA patients is between 7.2% and 11%. [1][2][3][4] Studies have shown that the survival rate declines rapidly when the duration of CPR surpasses 10 minutes and even more rapidly if it exceeds 30 minutes. 5,6 In some studies, 7-9 refractory cardiac arrest is thought to be present if, in the absence of preexisting hypothermia, return of spontaneous circulation (ROSC) is not achieved despite more than 30 minutes of appropriate CPR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 Internationally, EMS systems are utilizing SAED as either a stand-alone defibrillation strategy or in combination with manual defibrillation mode. [13][14][15] Although SAED results in faster times to defibrillation and higher cardioversion rates compared with manual defibrillation, 10,11 there are no studies that have translated these differences into better survival outcomes from OHCA. 16 Although previous studies have been limited by sample size, there is also some concern that SAEDs could increase pauses in chest compressions, and this could lead to poorer outcomes for OHCA patients, particularly in patients with initial nonshockable rhythms.…”
mentioning
confidence: 99%